Identification of radically different variants of porcine reproductive and respiratory syndrome virus in Eastern Europe: towards a common ancestor for European and American viruses - Stadejek, T.; Stankevicius, A.; Storgaard, T.; Oleksiewicz, M. B.; Belák, S.; Drew, T. W.; Pejsak, Z. (Journal of General Virology, 2002)
We determined 22 partial porcine reproductive and respiratory syndrome virus (PRRSV) ORF5 sequences, representing pathogenic field strains mainly from Poland and Lithuania, and two currently available European-type live PRRSV vaccines. Also, the complete ORF7 of two Lithuanian and two Polish strains was sequenced. We found that Polish, and in particular Lithuanian, PRRSV sequences were exceptionally different from the European prototype, the Lelystad virus, and in addition showed a very high national diversity. The most diverse present-day European-type PRRSV sequences were from Poland (2000) and Lithuania (2000), and exhibited only 72·2% nucleotide identity in the investigated ORF5 sequence. While all sequences determined in the present study were clearly of European type, inclusion of the new Lithuanian sequences in the genealogy resulted in a common ancestor for the European type virus significantly closer to the American-type PRRSV than previously seen. In addition, the length of the ORF7 of the Lithuanian strains was 378 nucleotides, and thus intermediate between the sizes of the prototypical EU-type (387 nucleotides) and US-type (372 nucleotides) ORF7 lengths. These findings for the Lithuanian PRRSV sequences provide support for the hypothesis that the EU and US genotypes of PRRSV evolved from a common ancestor. Also, this is the first report of ORF7 protein size polymorphism in field isolates of EU-type PRRSV.